The effect of various kinematics on postoperative pain after instrumentation: a prospective, randomized clinical study - Hakan Arslan; Ruslan Khalilov; Ezgi Doğanay; Ertugrul Karatas
ABSTRACT Objective: To evaluate various kinematic movements on postoperative pain using a Reciproc system. Material and Methods: Fifty-six molar teeth were divided into four groups according to kinematics as follows: continuous rotation, 360° CCW - 30° CW, 270° CCW - 30° CW, and 150° CCW - 30° CW. Preoperative and postoperative pain levels using visual analogue scale (VAS), percussion pain, and analgesic intake were recorded for each subject. Postoperative pain levels at 1, 3, 5, and 7 d were evaluated. Data were analyzed statistically using the Kruskal-Walis, Mann-Whitney-U, one-way analysis of variance, and chi-square tests (p=0.05). Results: Continuous rotation resulted in more pain at Day 1 when compared with the reciprocating groups (360° CCW - 30° CW and 270° CCW - 30° C) (p<0.05). Conclusions: Continuous rotation resulted in more postoperative pain at Day 1 than in reciprocating groups, and thereafter no significant pain was found among the groups.